Exploring Performance Differences Between UAS Sense-and-Avoid Displays. (September 2015) - Pack, Jessica S.; Draper, Mark H.; Darrah, Sara J.; Squire, Mark P.; Cooks, Andrea
The desire for Unmanned Aerial Systems (UAS) to routinely access manned airspace has grown substantially due to the proliferation of UAS and their associated applications. A key challenge to safely integrating UAS into the National Airspace System (NAS) is providing a reliable means for UAS to sense and avoid (SAA) other aircraft. The US Air Force is addressing this challenge through the Common Airborne Sense and Avoid (C-ABSAA) program. C-ABSAA is developing a sophisticated SAA capability that will be integrated onboard larger UAS. This paper summarizes key human factors efforts to develop a SAA traffic display with the appropriate level of information needed to aid the pilot in successfully maintaining self-separation and collision avoidance from other aircraft. The present study examined performance differences between candidate SAA displays as well as the most efficient manner to communicate recommended maneuvers. Fifteen Class 3-5 UAS military pilots compared five stand-alone SAA displays across two weather constraint levels (no weather, weather). Results indicated that the Banding Display tended to be most effective in aiding pilot performance during a SAA situation, with faster response times, less change in response time between weather conditions, no collision avoidance alert violations, and favorable subjective feedback. Implications of these findings on determining the acceptable level of information needed on a SAA display to aid pilot performance are discussed.